Penerapan Pelayanan Prima Islami dan Manajemen Berbasis Keamanan Terhadap Minat Berkunjung Kembali Pada Sektor Publik - Andrian, Andrian; Nilasari, Pratiwi (Jurnal Ilmiah Ekonomi Islam, 2023)
This study aims to determine the effect of Islamic excellent service (X1) and the strength of security-based management (X2) on revisit intentions (Y) in the community on public services in the East Bekasi District, Bekasi. The research methodology used is quantitative with the purposive sampling survey method for respondents who have the criteria of at least once visit and have experienced public services themselves. Then after collecting the necessary data, the data is processed by the researcher using statistical analysis, so that it can be seen whether the implementation of Islamic excellent service (X1) and security-based management (X2) has had a significant or not significant effect on revisit intentions (Y) to the public sectors. The value of the novelty of this research is to include and integrate Islamic excellent service (X1) with security management (X2) regarding on revisit intentions to the public sectors. The research results show that Islamic Excellent Service (X1) and Security-Based Management (X2) simultaneously have a significant effect on Revisit Intentions (Y) in Public Sectors in the East Bekasi District, Bekasi.